Transposon Dysregulation Modulates dWnt4 Signaling to Control Germline Stem Cell Differentiation in Drosophila - Upadhyay, Maitreyi (PLoS Genet, 2016)
Germline stem cell (GSC) self-renewal and differentiation are required for the sustained production of gametes. GSC differentiation in Drosophila oogenesis requires expression of the histone methyltransferase dSETDB1 by the somatic niche, however its function in this process is unknown. Here, we show that dSETDB1 is required for the expression of a Wnt ligand, Drosophila Wingless type mouse mammary virus integration site number 4 (dWnt4) in the somatic niche. dWnt4 signaling acts on the somatic niche cells to facilitate their encapsulation of the GSC daughter, which serves as a differentiation cue. dSETDB1 is known to repress transposable elements (TEs) to maintain genome integrity. Unexpectedly, we found that independent upregulation of TEs also downregulated dWnt4, leading to GSC differentiation defects. This suggests that dWnt4 expression is sensitive to the presence of TEs. Together our results reveal a chromatin-transposon-Wnt signaling axis that regulates stem cell fate.